A Nag‐like dioxygenase initiates 3, 4‐dichloronitrobenzene degradation via 4, 5‐dichlorocatechol in Diaphorobacter sp. strain JS3050. (10th November 2020) - Gao, Yi‐Zhou; Palatucci, Mallory L.; Waidner, Lisa A.; Li, Tao; Guo, Yuan; Spain, Jim C.; Zhou, Ning‐Yi
Summary: The chemical synthesis intermediate 3, 4‐dichloronitrobenzene (3, 4‐DCNB) is an environmental pollutant. Diaphorobacter sp. strain JS3050 utilizes 3, 4‐DCNB as a sole source of carbon, nitrogen and energy. However, the molecular determinants of its catabolism are poorly understood. Here, the complete genome of strain JS3050 was sequenced and key genes were expressed heterologously to establish the details of its degradation pathway. A chromosome‐encoded three‐component nitroarene dioxygenase (DcnAaAbAcAd) converted 3, 4‐DCNB stoichiometrically to 4, 5‐dichlorocatechol, which was transformed to 3, 4‐dichloromuconate by a plasmid‐borne ring‐cleavage chlorocatechol 1, 2‐dioxygenase (DcnC). On the chromosome, there are also genes encoding enzymes (DcnDEF) responsible for the subsequent transformation of 3, 4‐dichloromuconate to β‐ketoadipic acid. The fact that the genes responsible for the catabolic pathway are separately located on plasmid and chromosome indicates that recent assembly and ongoing evolution of the genes encoding the pathway is likely. The regiospecificity of 4, 5‐dichlorocatechol formation from 3, 4‐DCNB by DcnAaAbAcAd represents a sophisticated evolution of the nitroarene dioxygenase that avoids misrouting of toxic intermediates. The findings enhance the understanding of microbial catabolic diversity during adaptive evolution in response to xenobiotics released into the environment.